Impact of Appropriate Empiric Antibiotic Therapy on Outcomes in Patients with Pneumonia and Positive Blood vs. Respiratory Cultures. (4th October 2017) - Deshpande, Abhishek; Richter, Sandra S; Haessler, Sarah; Brizendine, Kyle; Lindenauer, Peter; Yu, Pei-Chun; Zilberberg, Marya D; Imrey, Peter; Higgins, Thomas; Rothberg, Michael
Abstract: Background: Receipt of appropriate antibiotics is an important determinant of length of stay and mortality. However, the impact of appropriate empirical therapy based on culture type (blood vs. respiratory) is unknown. Methods: We included adult patients admitted with pneumonia from 2010 to 2015 to 175 US hospitals if they had positive respiratory or blood cultures drawn by hospital day 1. Appropriate therapy was defined as an initial antibiotic that was effective against the recovered organism. Primary outcome was in-hospital mortality; secondary outcomes were transfer to ICU, initiation of vasopressors or invasive mechanical ventilation (IMV) after hospital day 2, and 30-day readmission. We used mixed logistic regression models to compare the impact of appropriate therapy based on blood or respiratory cultures adjusted for patient demographics, comorbidities, and severity of illness on admission. Results: Of 14, 125 patients with positive cultures, 6, 847 patients had positive blood and 7, 960 positive respiratory cultures; 91% of positive blood and 79% of positive respiratory culture patients received appropriate therapy. Compared with those receiving inappropriate therapy, patients receiving appropriate therapy were younger with fewer co-morbidities. Appropriate therapy was associated with significantly lower adjusted odds of inpatient mortality when based on blood (OR 0.61, 95% CI 0.48 – 0.77) but not respiratory cultures (OR 0.87, 95% CI 0.73 – 1.05). Appropriate therapy based on blood cultures was significantly associated with lower odds of subsequent ICU transfer (OR 0.72; 95% CI 0.53 – 0.98), vasopressors (OR 0.70; 95% CI 0.52 – 0.92), or IMV (OR 0.70; 95% CI 0.52 – 0.92) initiations, and 30-day readmission (OR 0.61; 95% CI 0.44 – 0.86). Appropriate therapy based on respiratory cultures was similarly associated with ICU transfer (OR 0.72; 95% CI 0.56 – 0.93) and vasopressor initiation (OR 0.77; 95% CI 0.62 – 0.95) but not 30-day readmission. Conclusion: In this large US cohort, appropriate therapy based on blood cultures was more strongly associated with mortality than appropriateness based on respiratory cultures. Prediction models for antibiotic resistance should be based on blood culture results. Disclosures: S. S. Richter, bioMerieux: Investigator, Research support; BD Diagnostics: Investigator, Research support; Roche: Investigator, Research support; BioFire: Investigator, Research support; OpGen: Investigator, Research support; S. Haessler, AHRQ: Investigator, Research grant; P. C. Yu, AHRQ: Investigator, Research grant; M. D. Zilberberg, Astellas: Consultant and Investigator, Research support; Merck: Consultant and Investigator, Research support; The Medicines Company: Consultant and Investigator, Research support; Shionogi: Consultant and Investigator, Research support; Pfizer: Consultant and Investigator, Research support; Theravance: Consultant and Investigator, Research support; J&J: Shareholder, Shareholder; M. Rothberg, AHRQ: Investigator, Research grant